Levofloxacin-Induced Oromandibular Dystonia in a 9-Year-Old Patient - Ghazavi, Mohammadreza; allameh, zahra (Iranian Journal of Child Neurology, 2024)
Extrapyramidal symptoms (EPS) that include akathisia, dystonia, pseudoparkinsonism, and dyskinesia are abnormal movements commonly induced by antipsychotic medications. These symptoms are also associated with specific non-antipsychotic agents. This case report describes a case of a 9-year-old boy on antibiotics treatment that developed EPS. A 9-year-old boy presented to the emergency department of Imam Hossein Children›s Hospital with chief complaints of trismus, difficulty speaking, and tongue protrusion. One week before these presentations, he had been prescribed Tavanex® (levofloxacin) and clindamycin. His symptoms improved after the withdrawal of antibiotics and administering Biperiden, and he was discharged in good condition. On a follow-up visit one week after discharge, no remaining symptoms were present, and he was in good condition. Based on the questions in the Naranjo criteria, levofloxacin receives a score of 7 and is a probable cause of adverse drug reaction (ADR). Clindamycin, with a score of 6, is also a probable cause for this adverse drug reaction, but clinical judgment was in favor of levofloxacin as the culprit. Clinicians should be aware of the potential EPS of levofloxacin at standard doses. Effective management of adverse events is necessary to ensure patient safety and optimal outcomes